2016
DOI: 10.1159/000448001
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of Ginsenoside Rg3 in a Rat Model of Incisional Pain

Abstract: Background: Ginsenoside Rg3 is an extract of total ginseng saponins, which accounts for 4.7% of all saponins. This study aimed to identify the mechanisms of the antinociceptive effects of ginsenoside Rg3. Methods: Rats were randomly divided into six groups, which were treated with vehicle or 0.5, 1, 1.5, 2, or 4 mg/kg of ginsenoside Rg3 intraperitoneally 2 h after a plantar incision was made. To evaluate the mechanisms of antinociceptive effects, the rats were intraperitoneally injected with naloxone 5 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…These include the effects of R3 (20(s)-Rg3 isomer) on plantar incisional pain in an adult Sprague-Dawley rat model. Inflammatory cytokines levels closely correlated with the pain response ( Figure 35) [113], protection against cigarette smoke extract-induced cell injury in a preconditioning protocol [114], the biphasic enhancement of glucose-stimulated insulin secretion, and AMPK activities by both the 20R and 20S isomers [115] and protection against glutamate-mediated neuronal cell death to HT22 cells, a mouse hippocampal cell line ( Figure 36) [106], and protected against ginsenoside induced cell toxicity in Sprague-Dawley fetal cortical cells. With respect to the biphasic dose response for plantar incision pain, the authors suggested that this could make it more challenging for use in a therapeutic application, noting further the need to document the biphasic dose response in humans.…”
Section: Rg3mentioning
confidence: 85%
See 2 more Smart Citations
“…These include the effects of R3 (20(s)-Rg3 isomer) on plantar incisional pain in an adult Sprague-Dawley rat model. Inflammatory cytokines levels closely correlated with the pain response ( Figure 35) [113], protection against cigarette smoke extract-induced cell injury in a preconditioning protocol [114], the biphasic enhancement of glucose-stimulated insulin secretion, and AMPK activities by both the 20R and 20S isomers [115] and protection against glutamate-mediated neuronal cell death to HT22 cells, a mouse hippocampal cell line ( Figure 36) [106], and protected against ginsenoside induced cell toxicity in Sprague-Dawley fetal cortical cells. With respect to the biphasic dose response for plantar incision pain, the authors suggested that this could make it more challenging for use in a therapeutic application, noting further the need to document the biphasic dose response in humans.…”
Section: Rg3mentioning
confidence: 85%
“…The range of endpoints assessed has been broad but dominated by the area of neuroprotection. The areas of greatest interest have been those dealing with cellular/animal models for AD [48] and PD [41,42] disease, followed by stroke [51,52,152,153], neuronal health/regeneration based on studies with spinal cord [24,107]/sciatic nerve [62] injuries, and pain [113]. It is remarkable that this broad range of endpoints from a similarly wide variety of biological models and experimental approaches (e.g., pre-post-conditioning, non-conditioning, different mediators of damage) display hormetic dose responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive activation of hERG1 would cause early repolarization of action potentials, essentially mimicking congenital short QT syndrome, a disorder of ventricular repolarization that also increases the risk of lifethreatening arrhythmia (Gaita et al, 2003;Shah, 2010). Rg3 and related ginsenosides have been extensively studied and are claimed to exert a multitude of therapeutic effects (Weber et al, 2012;Nah, 2014;Ahn et al, 2016). Given the plethora of activities associated with Rg3, it is not surprising that this ginsenoside is not a hERG1-specific compound.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly since the red ginseng fraction we used in our study is enriched in Rg3 so we would like to elucidate the effects of Rg3 as an antinociceptive because it modulates the Ca 2+ channels (part of the pharmacologic basis of ginseng-mediated antinociception) and as an anti-inflammatory agent in the suppression of mouse ear swelling and prevention of vascular inflammatory diseases by decreasing the expression of intercellular adhesion molecule 1 (ICAM–1), vascular cell adhesion molecule-1 (VCAM-1), and P- and E-selectin [ 5 8 ]. Moreover, Rg3-induced apoptosis in A549 lung adenocarcinoma via downregulation of epidermal growth factor receptor and in human breast cancer (MDA-MB-231) cells, thus preventing breast cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%